Praktik penyusunan proyek penguatan profil pelajar Pancasila (P5) dan PPRA (Profil Pelajar Rahmatan Lil Alamin) - putra, ridho arifin (Maliki Interdisciplinary Journal, 2026)
This study discusses the implementation of the Rahmatan lil Alamin Student Profile Strengthening Project (PPRA) as an effort to strengthen students’ character within the Merdeka Curriculum. The P5 program is a project-based learning approach designed to help students develop in accordance with Pancasila values, such as belief and devotion to God Almighty, mutual cooperation, independence, critical thinking, creativity, and global diversity awareness. Meanwhile, PPRA emphasizes the development of moderate, tolerant, and humanistic religious character within the madrasah environment. This study employs a literature review method by examining various scientific sources related to the implementation of P5 and PPRA in education. The findings indicate that the implementation of these two programs has a positive impact on students’ character development through project-based learning, the habituation of religious values, school culture, as well as intracurricular and cocurricular activities. In addition, these programs help students develop critical, creative, and collaborative thinking skills while fostering attitudes of tolerance and social awareness. However, the implementation of these programs still faces several challenges, including teachers’ limited understanding, inadequate facilities and infrastructure, and the lack of optimal collaboration among schools, parents, and the community. Therefore, strengthening efforts are needed through teacher training, learning innovation, and support from various stakeholders so that P5 and PPRA can be implemented effectively and sustainably.